The Effectiveness of CapCut in Increasing Student Inte-rest in Quran Hadith Subjects in Elementary Schools - Rabbani, Khafidh Fardan; Fathoni, Achmad (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: The purpose of this research is to find out (1) how students are affected by conventional learning; (2) how students are affected by learning using Cap-cut Application; and (3) how well the effectiveness of Capcut Application works in increasing students' interest in learning Al Qur'an Hadith. Methodology: This type of research uses a comparative quantitative approach, namely com-paring before using the Capcut Application and when using the Capcut Ap-plication. The data collection technique uses a sample of 2 classes, namely class 4.1 and class 4.2 totaling 40 students, the data collection technique us-es a questionnaire, with analysis techniques including validity, reliability, normality, homogeneity and t tests (independent sample tests and paired sample tests), researchers also test their knowledge and skills directly. Results: The results of the paired samples test output above show that the Sig value is known. (2-tailed) 0.000 (<0.05), then H0 is rejected, Ha is accepted. This hypothesis test shows that there is a difference in learning interest between learning classes using Capcut and conventional classes. With the difference in the average value of learning interest, it shows that there is an effect of using Capcut in learning, so the conclusion is that Capcut is effective for in-creasing students' interest in learning Al Quran Hadith subjects in elementary schools. Therefore, there is a considerable difference between the mean (average) value of students' interest in learning before and after treatment as shown by the comparison results. Applications/Originality/Value: In the application of learning using this Capcut Application, the teacher must first master the Capcut Application with the aim of being effective in increasing interest in learning to students in the subject of Al Quran Had-ith.